تطوير مادة البلاغة على ضوء المدخل التقابلي بجامعة الأزهري شيأنجور - Hermawan, Acep (Jurnal Pendidikan Islam, 2016)
The research is an exploratory study to real condition STAI Cianjur students who find the difficulties while Balagha by using the book which is intended for the native Arabs. Due to that reason, the researcher considers that it is necessary to design Balagha Curriculum which is easily understood by the students in Indonesia. The solution proposed is presenting the materials of Balagha contrastively: that is, by comparing the similarities and differences with Indonesian Language system. The method used in this study is quasiexperimental methods. The experiments were carried out through giving pre-test and post-test to the students. Pre-test is to determine students’ prior understanding before the contrastive approach in learning Balagha is implemented. Post-test is to determine students’ comprehension after the use of the approach. The result shows that presenting Balagha materials through contrastive approach improves students’ learning outcomes significantly. Thus, the development of Balagha teaching materials through contrastive approach can improve students’ understanding of Balagha materials.